- #1

wajed

- 57

- 0

I know that x= -/+ sqrt(y)

but I don`t understand why I do this every time I try to solve "y=x^2" for "x".

I know the fact that -2^2=4, and also 2^2=4. and that is why we must have two answers, but I just need to understand how the process really goes, I just want to know the flaw of the logical steps that lead to the conclusion that x=-/+ sqrt(y).

I think its about inverse functions, and when I asked my question on Yahoo! answers, I got this answer:

The inverse of a function f(x) is defined as

f(f^-1(x)) = x

If f(x) = x^2

then f(f^-1(x)) = [f^-1(x)]^2

but f(f^-1(x)) =x ... so [f^-1(x)]^2 = x

f^-1(x) = +/- SQRT(x)

I just don`t get how he`s done the last step!

huh, it really doesn't make sense to me, since he just applied the inverse -which in this case is sqrt. function- on the last step, which is the thing I`m actually trying to understand how it happened!

PS: I`m sorry, I haven`t studied mathematics thoroughly before, nor have I studied logic..

So, actually I don't know if I could put my question in a better way, because I don`t even know where is the problem specifically,

I`m just a high school student, trying to understand something out of his book, because he is burning to hell to know how this is happening.